Comparative Study by Experiment of Design Cooling System Between Air Cooling and Water Spray Cooling Method for Optimization of Solar Photovoltaic - Ananda, Galieh; Hakim, Mohamad Dimas Nur; Wulandari, Rindi (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2024)
Solar photovoltaic is a renewable energy that has great potential and is quite cheap. However, solar cells are sensitive to temperature through the parameters of their semiconductor materials. The optimal solar photovoltaic temperature range is 25◦C- 40◦C. Based on the study, the optimal temperature of the solar photovoltaic system is 41◦C. The problem is that solar photovoltaics do not produce power optimally when the surface temperature reaches 41◦C so the power produced decreases. The cooling system is one solution to overcome temperature problems in solar photovoltaics. The purpose is to design an automatic cooling system based on water and air spray using Arduino Uno which operates only at solar photovoltaic surface temperatures above 41◦C and compare the working effectiveness of the cooling system using water spray and air when the surface of the solar photovoltaic reaches maximum heat and does not work optimally. Methods. Design and develop a water and air-spray-based cooling system using an experimental process. Results. The automatic cooling system has been designed using a water spray cooling method and a DC fan-based air cooling method. The water spray cooling method can reduce the temperature optimally with an average temperature of 38.67◦C and the air cooling method can reduce the temperature optimally with an average temperature of 39.5◦C. The water spray cooling method had an efficiency value of 36% and the DC fan-based water cooling method had an efficiency value of 16%.